A case study on the performance of Bachelor of Accountancy (HONS) students of UiTM Kampus Arau: The effects of gender, past performance and campus origin / Normah Ahmad … [et al.] - Ahmad, Normah; Amiruldin, Roselina; Wan Zakiuddin, Wan Madihah; Mohd Noor, Azura (Universiti Teknologi MARA, Perlis, 2003)
A research was carried out on the effects of gender, past performance and campus origin on the performance of Bachelor of Accountancy (Hons) students of UiTM Kampus Arau. The students were those of the 1997, 1998 and 1999 intakes who would have graduated in the year 1999, 2000 and 2001 respectively. Using the independent sample test, correlation, regression and AN OVA, the researchers found that past performance greatly influences the present performance of the bachelor degree students. Students who scored a good grade at diploma level would continue to perform well at the degree level. However, gender and campus origin are not significant in explaining the present performance of these students. These results varied with some other research which proved otherwise. (Examples Mutchler and Williams, 1987; Borde, 1998; Tyson, 1989). Nevertheless, there is a need for the Faculty of Accountancy to consider the research results in developing enrolment policies for the bachelor programme and in fulfilling a request made by students for a transfer from one campus to another.